The Use of Microsoft Teams during Distance Learning and Its Impact on Increasing Students’ Reading Interest - Anggraita Pangriptaningrum; Hermanto (Universitas Pendidikan Ganesha, 2022)
Due to the COVID-19 pandemic, all education units in Indonesia have implemented distance learning programs. This requires schools to use learning platforms to enhance teacher and student learning interactions. Therefore, it is necessary for teachers to make learning more interesting and achieve learning objectives with available platforms. This study aims to analyses more deeply learning designs utilizing Microsoft Teams within distance learning to increase reading interest in lower grade students during the pandemic. Descriptive qualitative methods are applied as the approaches to describe and explain the actual circumstances. The research subject consisted of 5 teachers, 10 students, and 10 parents. The method of data collection in this study is to use observations and interviews were conducted online employing Google Form or phone due to the Covid-19 pandemic occurred in Indonesia during the research. The analysis technique used is descriptive qualitative. The result shows the effectiveness of Microsoft Teams for the online learning in enhancing lower grade students’ reading interests. The interesting features offered in it also make it easier for teachers and students to perform teaching and learning activities, while parents can participate in monitoring their children's learning progress as well. Suggestion: parents can also participate to monitor activities and developments in learning process.